Penerapan Metode Hybrid Case Base Pada Sistem Pakar Diagnosa Penyakit Jantung - Ayu Handayani; Jeperson Hutahaean; Akmal Nasution (Forum Kerjasama Pendidikan Tinggi, 2022)
Many people have died of sudden heart attacks. The role of a specialist doctor is very necessary to overcome this, but the role of the doctor is also bumped due to limitations in terms of numbers and hours worked. In addition, in general, people with heart disease often ignore and do not understand the causes and symptoms of heart disease. Most patients are reluctant to have their heart health checked because they are constrained by expensive medical expenses, as well as a lack of service to patients. In the process of consulting for heart disease, the patient must come to the hospital and do an examination in person which of course must go through a series of procedures starting from registration onwards to get results. To overcome this problem, an expert system application is needed for the early diagnosis of heart disease. The purpose of this study was to build a web-based system of heart disease diagnosis expert applications. This expert system application uses the Hybrid Case Base method which is a combination of the Rule-Based Reasoning (RBR) and Case-Based Reasoning (CBR) systems. The RBR system and the CBR system have their advantages and disadvantages. The analysis and design of the systems used are UML and Entity Relationship Diagrams. In this expert system application, patients will consult by answering several questions about the symptoms of heart disease displayed by the system by checking the symptoms they experience. Then the system will provide diagnostic results based on the symptoms experienced by the patient. The results of this study can diagnose the type of heart disease experienced by patients and their treatment solutions and what percentage of the patient is likely to suffer from the disease quickly